1982
DOI: 10.1007/bf01341726
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic relationships between rotaviruses from different species as studied by neutralization and immunofluorescence

Abstract: Antigenic relationships between the Wa, Hochi, Ito, Hosokawa and Nemoto strains of human rotavirus, the SA-11 strain of simian rotavirus, the Lincoln strain of bovine rotavirus, the OSU strain of porcine rotavirus and the R-2 strain of lapine rotavirus, which were all established in cell culture, were studied by neutralization (NT) and immunofluorescence (IF) using guinea pig antisera against these strains. The strains could not be distinguished by indirect IF staining of infected cells because of marked cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
2

Year Published

1984
1984
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 22 publications
2
32
2
Order By: Relevance
“…The cross-reactions between PP-1 and the porcine virus suggests that rotaviruses from cattle and pigs may not be antigenically distinct as suggested by Thouless et al (1977) and Sato et al (1982). Some other rotaviruses from different animal species cross-react antigenically in typespecific tests either in a one-or two-way fashion, e.g.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The cross-reactions between PP-1 and the porcine virus suggests that rotaviruses from cattle and pigs may not be antigenically distinct as suggested by Thouless et al (1977) and Sato et al (1982). Some other rotaviruses from different animal species cross-react antigenically in typespecific tests either in a one-or two-way fashion, e.g.…”
Section: Discussionmentioning
confidence: 97%
“…For example, rotaviruses which share a common group antigen from different animal species can be distinguished by neutralization tests (Thouless et al, 1977;Estes & Graham, 1980;Sato et al, 1982), suggesting some degree of species specificity. However, inter-species transmissions (for review, see McNulty, 1978), cross-protection between rotaviruses or by antibody-containing fluids from different species (Wyatt et aL, 1979;Bartz et al, 1980;Bridget & Brown, 1981) and antigenic cross-relationships between some rotaviruses from different animal species (Bastardo et al, 1981 ;Gaul et al, 1982;Hoshino et al, 1982Hoshino et al, , 1983 indicate that rotaviruses may not all be species-specific.…”
Section: Introductionmentioning
confidence: 99%
“…NT was carried out in tube cell cultures essentially as previously described (Sato et al, 1982). Rotavirus of serotype 1 (Wa strain), serotype 2 (DS-1 strain) and serotype 3 (SA-11) were activated with 10 p.g/ml trypsin (14900 units/mg) at 37 °C for 30 min before use.…”
Section: Seramentioning
confidence: 99%
“…YO, MO, ITO, Nemoto, P2 and S3, isolated from Japan [Kutsuzawa et al, 1982;Sato et al, 1982;Urasawa et al, 1982]; P and M from USA; Pz, RV from Australia [Wyatt et al, 1983]; and AK-35 from Kenya [Urasawa et al, 1987], several other G3 isolates from humans showed closeness to animal G3 strains, especially to feline and canine rotaviruses. For example Japanese strains, AU-1 and AU228 showed close homology to a feline G3 strain FRV-1 [Nakagomi et al, 1987;Nakagomi and Nakagomi, 1989], while HCR3 strain from Philadelphia USA, to feline FRV64 and canine strains CU-1 and K9 [Nakagomi et al, 2000].…”
Section: Discussionmentioning
confidence: 97%